Rozwiąż równania:
a) 2(3x −1) − (4x − 3) + x = 5(x + 2) − 3(x − 2) −15
b) 3x/4 - 1+x/2 = 3/8 - x

Rozwiąż nierówności:
a) 2(3x − 5) + 2(1− x) > 3 − 4(2 − x)

b) 2x - 3(x-1)/2 _< x-1

(W przykładzie b, znak jest "mniejsze lub równe")

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-08T22:04:42+02:00
Równanie
a) 6x-2-4x+3+x=5x+10-3x+6-15
6x-4x+x-5x+3x=10+6-15+2-3
x=0
b)3x/4-1+x/3=3/8-x
????
nierówność
a)6x-10+2-2x>3-8+4x
6x-2x-4x>3-8+10-2
0x>3
rozwiązanie sprzeczne x≠0
b) 2x-3(x-1)/2≤x-1
2x-(3x+3)/2≤x-1 /*2
4x-6x+6≤x-1
4x-6x-x≤-1-6
-3x≤-7 /÷ -3
x≥7/3
x≥1⅓